KIPRAH DAN PERJUANGAN K.H MAS MANSUR DALAM PERSERIKATAN MUHAMMADIYAH PADA TAHUN 1916-1946 - Sofyan Hanafi; Kuswono Kuswono (Swarnadwipa, 2020)
The purpose of this study was to determine the background of KH Mas Mansur's life, to know the progress of K.H Mas Mansur in the Muhammadiyah organization in 1916-1946, and to know the struggle of KH Mas Mansur in the Muhammadiyah Association as general chairman in 1937-1947. This research approach is historical research. This research method using heuristict, library study, and data intepretation method. The result of this research is that KH Mas Mansyur was born from a trader who is quite rich and famous. He was raised in a boarding school environment so that the religious education he received was maximized. His knowledge of religion is very broad, to support this, Mas Mansyur continued his education in Cairo, Egypt. KH Mas Mansyur's progress in the Muhammadiyah union was very much, at first he became a member of Muhammadiyah, then chairman of the branch in Surabaya, until he became chairman of Muhammadiyah. Many of its struggles during the Muhammadiyah union were also very many, including sparking twelve Muhammadiyah steps in achieving its goals.